Multiple Auger cycle photoionisation of manganese atoms by short soft x-ray pulses. (6th April 2017) - Klumpp, S; Gerken, N; Mertens, K; Richter, M; Sonntag, B; Sorokin, A A; Braune, M; Tiedtke, K; Zimmermann, P; Martins, M
Abstract: The multiple ionisation of atomic Mn, excited at (photon energy: 52.1 eV) and above (photon energy: 61.1 eV) the discrete giant 3 p – 3 d resonance, was studied using high irradiation free-electron-laser soft x-ray pulses from the BL2 beamline of FLASH, DESY, Hamburg. In particular, the impact of the giant resonance on the ionisation mechanism was investigated. Ion mass-over-charge spectra were obtained by means of ion time-of-flight spectrometry. For the two photon energies, the yield of the different ionic charge states Mn q + ( q  = 0–7) was determined as a function of the irradiance of the soft x-ray pulses. The maximum charge state observed was Mn 6+ for resonant excitation at 52.1 eV and Mn 7+ for non-resonant excitation at 61.1 eV at a maximum irradiation of 3 × 10 13 W cm − 2 .